2005
DOI: 10.1111/j.1365-2265.2005.02325.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypocortisolism in survivors of severe acute respiratory syndrome (SARS)

Abstract: These preliminary findings highlight a possible aetiologic role of SARS-associated coronavirus in causing a reversible hypophysitis or direct hypothalamic effect, with the HPA axis affected more frequently than the HPT axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
256
1
20

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(309 citation statements)
references
References 34 publications
6
256
1
20
Order By: Relevance
“…Therefore, the hypothalamuspituitary dysfunction may be the underlying cause of low serum TSH. Leow et al [10] reported that 4 of 61 SARS survivors (6.7%) were hypothyroid including 3 cases with central hypothyroidism and 1 with primary hypothyroidism with positive autoimmune antibodies. In addition to hypothyroidism, they reported a more frequent occurrence of central hypocortisolism in a substantial number of patients with SARS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the hypothalamuspituitary dysfunction may be the underlying cause of low serum TSH. Leow et al [10] reported that 4 of 61 SARS survivors (6.7%) were hypothyroid including 3 cases with central hypothyroidism and 1 with primary hypothyroidism with positive autoimmune antibodies. In addition to hypothyroidism, they reported a more frequent occurrence of central hypocortisolism in a substantial number of patients with SARS.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of patients with SARS have shown abnormalities in either of these 2 functions, which lends support to the supposition that SARS has a harmful effect on the thyroid gland. In some cases, decreased T3 and T4 serum levels were detected suggesting follicular cell dysfunction [9,10]. In other cases, osteonecrosis of the femoral head was found in recovered patients with SARS, which may have been caused by a decrease of inhibition of osteoclasts resulting from calcitonin deficiency [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…During the SARS outbreak in 2003, four healthcare workers from one hospital contracted the disease and were treated with corticosteroids that resulted in the development of ONFH [11,12]. All patients were treated with cocktail therapy that consists of ESWT, hyperbaric oxygen therapy (HBO) (2.5 ATA in 15 min) and oral alendronate (70 mg of oral alendronate sodium) [12].…”
Section: Eswt and Cocktail Therapy For Onfhmentioning
confidence: 99%
“…Severe acute respiratory syndrome (SARS) was one of the most challenging public‐health crises faced in Hong Kong in 2003, infecting 1755 people and claiming 299 lives . Many SARS survivors are still suffering physical, functional, and psychological and behavioural disorders after the acute infection, which requires long‐term medical attention and reached a chronic phase.…”
Section: Introductionmentioning
confidence: 99%